Levels of Galectin-3 and Stimulation Expressed Gene 2 in the peritoneal fluid of women with endometriosis: a pilot study. (December 2014) - Caserta, Donatella; Di Benedetto, Luisa; Bordi, Giulia; D'Ambrosio, Angelo; Moscarini, Massimo
Abstract Endometriosis is a puzzling disorder with obscure pathogenesis. Several studies suggest that peritoneal fluid is a key inflammatory environment in the development and progression of the disease. This study analyzed the levels of two inflammatory factors – Galectin-3 and Stimulation Expressed Gene 2 – in the peritoneal fluid of 15 women affected by endometriosis and 8 controls. The peritoneal fluid was collected during laparoscopic surgery avoiding any form of contamination and it was properly processed and stored. Gal-3 and ST2 peritoneal concentrations were analyzed using enzyme immunoassay kit. Gal-3 levels were significantly higher in endometriosis group than in controls (64.7 ± 52.34 versus 21.05 ± 20.83 ng/ml, p = 0.044), whereas ST2 concentrations did not differ between the two groups. A significant positive correlation was found between Gal-3 and ST2 levels. Gal-3 levels positively correlated with the stage of endometriosis, the duration of symptoms, Marinoff scale and VAS score, while ST2 levels were positively associated with VAS score. Our results suggest that Gal-3 and ST2 could be implicated in the inflammatory process of the disease. Further studies are needed to identify markers of early diagnosis and to open new therapeutic avenues in endometriosis.